Synthesis and characterization of hyperbranched polyglycerols with various degree of methylation employing phase-transfer conditions. (16th August 2021) - Neumann, Niklas; Boskamp, Laura; Hartwig, Andreas; Koschek, Katharina
Abstract: A simple method for partial methylation of the hyperbranched polyglycerol hydroxyl groups was achieved by a combination of phase-transfer catalysis approach with dimethyl sulfate and tetrabutylammonium bromide and the use of a mixed-bed ion exchanger for purification. Various degrees of methylation between 0 and 98% could be adjusted in a controlled manner via the added amount of alkylating agent resulting in modified polymers with moderate polydispersities. NMR spectroscopy was used to determine the methylation progress and the resulting molecular structure. The methylation degree affected associative intra- and intermolecular interactions, such as hydrogen bonds, entailing reduced glass transition temperature and viscosities with increasing hydroxyl group conversion. In addition, the attenuation of hydrogen bonds upon methylation proved to facilitate a straightforward estimation of methylation degree by infrared spectroscopy. Graphical abstract: Image 1 Highlights: Hyperbranched polyglycerol with degree of methylation between 0 and 98%. Two step synthesis for a targeted and adjustable methylation. Decreasing hydroxyl group content causes decrease in T g and viscosity. Beneficial combination of alkylating agent and mixed-bed ion exchanger for work-up.